Effect of direct–current biasing on the adjustable radio-frequency negative permittivity characteristics of Bi2SiO5/multiwall carbon nanotube metacomposites. Issue 1 (1st January 2021) - Haldar, Toton; Kumar, Utkarsh; Yadav, B.C.; Kumar, V.V. Ravi Kanth
Abstract: Multiwall carbon nanotube (MWCNT) based metacomposites with negative permittivity have received significant interest over the past decade due to their unique electromagnetic properties. Here, markedly percolating Bi2 SiO5 (BSO)/MWCNT metacomposites with adjustable negative permittivity were prepared by the facile hydrothermal method. Three-dimensional conductive networks formed by interconnected MWCNT are present in BSO/MWCNT metacomposites with 10 and 20 wt% of MWCNT. The detailed microstructure and resistivity studies of the metacomposites led to realize that the adjustable negative permittivity of the BSO/MWCNT metacomposites attributes to the low-frequency plasmon resonance of free Drude carriers. In this work, the effect of the direct-current biasing voltage in the radio frequency region is investigated on the negative permittivity characteristics. For below percolation threshold ( f c ) metacomposites, the Maxwell-Wagner polarization effects increase in low-frequency region immediately after dc bias is applied. In case of above percolation threshold ( f c ) metacomposites, the Drude free carrier concentration increases due to the formation of conductive network among MWCNT led to the rise of negative permittivity values in the low frequency region. This work provides a novel strategy for the adjustment of the negative permittivity value, which can expand the potential application in the field of sensors based on the changes in permittivity properties. Graphical abstract: Image 1